Cycle Partitions in Dense Regular Digraphs and Oriented Graphs - Allan Lo; Viresh Patel; Mehmet Akif Yıldız (Forum of Mathematics, Sigma)
A conjecture of Jackson from 1981 states that every d-regular oriented graph on n vertices with